Peran Sistem Informasi Manajemen Dalam Meningkatkan Daya Saing Usaha Mikro Kecil Dan Menengah (UMKM) - Syafrina, Angelia Putri; Nasution, Muhammad Irwan Padli (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the role of Management Information Systems (MIS) in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. The development of information technology has provided great opportunities for MSMEs to expand markets, improve operational efficiency, and strengthen customer relationships. The implementation of MIS assists MSME actors in effectively managing data, accelerating decision- making, and increasing productivity. Through integrated information systems, MSMEs can compete with larger companies by applying data-driven and innovation-based strategies. This research uses a descriptive approach with a literature study from various relevant academic sources. The results show that MIS plays a crucial role in strengthening MSME competitiveness through efficiency, transparency, and adaptability to market changes.